Creating Ethical Behaviors In Nursing Management - Arzu Hakko; Meral Madenoğlu Kıvanç (Association of Nurse Managers, 2018)
By searching literatures, primarily, nursing management and the frame of ethical concept and the importance of creating ethical behaviours in nursing management were investigated. In the light of previous studies, this study would like to draw attention to the importance of respect to humans, authority, autonomy, utilitarianism, not behaving badly, justice and loyality principles. Therefore, it has aimed to guide nursing managers how to manage ethical codes about the subjects on workers selection, training, development, orientation and motivation. The main objective of nurses is treating patients perfectly. The objective of nursing managers should be realizing quality of professional service and productivity targets simultaneously. The nurses caring patients by the ethical principles is also providing them being professional in their field. They should be managed by ethical codes in the processes of hiring, training, performance evaluation and awarding to achieve a nursing care by the respect to the human beings with the basic ethical principles. In conclusion, as it should be in all maganement systems, nursing managers also should use their authority by determining standarts with the ethical codes. This would achieve institutions to their goals and also it would be helpful to the workers, patients and the community simultaneously.